Antibody response after first and second-dose of ChAdOx1-nCOV (CovishieldTM®) and BBV-152 (CovaxinTM®) among health care workers in India: The final results of cross-sectional coronavirus vaccine-induced antibody titre (COVAT) study - Singh, Awadhesh Kumar; Phatak, Sanjeev Ratnakar; Singh, Ritu; Bhattacharjee, Kingshuk; Singh, Nagendra Kumar; Gupta, Arvind; Sharma, Arvind (Vaccine, 2021)
•This study evaluated the humoral antibody response after first and second doses of SARS-CoV-2 vaccine CovishieldTM and CovaxinTM in Indian health-care workers.•Combined results of both vaccines showed 95% seropositivity to anti-spike antibody, 21–36 days after the second completed dose.•Seropositivity rates were higher in Covishield recipients compared to Covaxin in the propensity-matched analysis of SARS-CoV-2 naïve participants.•Gender, presence of comorbidities and the type of vaccine received were independent predictors of antibody response after the second dose. We assessed the humoral immune response of both ChAdOx1-nCOV (CovishieldTM) and BBV-152 (CovaxinTM) vaccines in Indian health care workers (HCW). A Pan-India, Cross-sectional, Coronavirus Vaccine-induced Antibody Titre (COVAT) study was conducted that measured SARS-CoV-2 anti-spike binding antibody quantitatively, 21 days or more after the first and second dose of two vaccines in both severe acute respiratory syndrome (SARS-CoV-2) naïve and recovered HCW. Primary aim was to analyze antibody response (seropositivity rate, Geometric Mean Titre [GMT] and 95% Confidence Interval [CI]) following each dose of both vaccines and its correlation to age, sex, blood group, body mass index (BMI) and comorbidities. Here we report the results of anti-spike antibody response after first and two completed doses. Among the 515 HCW (305 Male, 210 Female) who took two doses of both vaccines, 95.0% showed seropositivity to anti-spike antibody. However, both seropositivity rate and GMT (95% CI) of anti-spike antibody was significantly higher in Covishield vs. Covaxin recipients (98.1 vs. 80.0%; 129.3 vs. 48.3 AU/mL; both p < 0.001). This difference persisted in 457 SARS-CoV-2 naïve and propensity-matched (age, sex and BMI) analysis of 116 participants. Age > 60-years, males, people with any comorbidities, and history of hypertension (HTN) had a significantly less anti-spike antibody GMT compared to age ≤ 60 years, females, no comorbidities and no HTN respectively, after the completion of two doses of either vaccine. Gender, presence of comorbidities, and vaccine type were independent predictors of antibody seropositivity rate and anti-spike antibody titre levels in multiple logistic and log transformed linear regression analysis. Both vaccine recipients had similar solicited mild to moderate adverse events and none had severe or unsolicited side effects. Both vaccines elicited good immune response after two doses, although seropositivity rates and GMT of anti-spike antibody titre was significantly higher in Covishield compared to Covaxin recipients.